Co-creating Artificial Intelligence: Designing and Enhancing Democratic AI Solutions Through Citizen Science - Annelies Duerinckx; Carina Veeckman; Karen Verstraelen; Neena Singh; Jef Van Laer; Michiel Vaes; Charlotte Vandooren; Pieter Duysburgh (Citizen Science: Theory and Practice)
Although artificial intelligence (AI) is omnipresent in our everyday lives, the level of awareness and knowledge among the general population remains mixed. The lack of understanding is particularly prevalent among older adults, and people with a low education and income. To bridge this knowledge gap and to empower individuals to become informed AI users, further outreach and awareness raising is necessary. This article presents a case study in Flanders (Belgium), called the amai! program (Flemish slang for “oh my!”). The program invites participants to voice their ideas or societal problems they wish to solve through AI and to be involved in the development of citizen-driven research projects. Using a citizen science (CS) approach, ideas are collected through a centralized platform and eventually realized through an open project call with partners from industry, civil society, and research institutions. As a result, 988 ideas have been submitted through the program’s platform and 14 are being realized in the domains of mobility, climate, health, and work. Here, we outline a phase-based approach for setting up citizen-driven research projects, as well as lessons learned on how to sensitize and activate citizens. Guidelines are also provided on how to involve participants to become aware and learn about science and technology, especially those with no prior knowledge or interest. Overall, this case study demonstrates how AI innovation and governance can be democratized through citizen participation and can build capacities in a fun and accessible way.